2016
DOI: 10.1590/s0102-865020160090000003
|View full text |Cite
|
Sign up to set email alerts
|

Oral or topical administration of L-arginine changes the expression of TGF and iNOS and results in early wounds healing

Abstract: Brazil. Design of the study, statistical analysis, analysis of data, manuscript writing. ABSTRACT PURPOSE:To evaluate the contribution of L-arginine oral or topical rout of administration in the surgical wound healing process.METHODS: L-arginine was orally or topically administrated to mice after a laparotomy model procedure. The wounds were analyzed to evaluate the granulation tissue by HE analysis, collagen deposition, iNOS and cytokines production by immunochemisyry on wound progress. Mice used in this mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Arginine with a dose of 8 mM effectively decreased IL-8 in the IPEC-J2 cells induced by LPS ( Lan et al , 2020 ). Another study also found that the administration of arginine topical showed low levels of IL-8 in laparotomy mice ( Jeronimo et al , 2016 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Arginine with a dose of 8 mM effectively decreased IL-8 in the IPEC-J2 cells induced by LPS ( Lan et al , 2020 ). Another study also found that the administration of arginine topical showed low levels of IL-8 in laparotomy mice ( Jeronimo et al , 2016 ).…”
Section: Discussionmentioning
confidence: 92%
“…This result is in line with a study by Zhou et al (2012) in endotoxemic rats, which showed a decrease in IL-10. Arginine supplementation only showed that topical administration did not affect IL-10 production in mice with laparotomy ( Jeronimo et al , 2016 ). In Contrary, several studies showed that glutamine only affects the high production of IL-10 in lobectomy patients ( Wang et al , 2018 ) and in bone marrow-derived macrophages induced by LPS ( de Oliveira et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…l -arginine orally or topically improved wound repair; however, the oral administration showed a higher NOS and TGF-β expression, and a significant decrease in inflammatory response. In addition, some studies showed that systemic l -arginine was more efficient than topical l -arginine in wound healing (Zandifar et al 2015 ; Jerônimo et al 2016 ; Witte et al 2002 ; Heffernan et al 2006 ). For this reason, the oral supplement was our option to treat the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Admittedly, oral Haruan supplement has a higher amount of concentrate which is believed to yield more merits compared to eating the flesh itself. Besides, for surgical or major traumatic wounds that involve multiple tissue layers, oral administration of Haruan extract is deemed superior to topical application [65,66]. The detailed steps in the preparation of Haruan capsules are described in Figure 4.…”
Section: Haruan Capsulesmentioning
confidence: 99%